Ground clutter cancellation in incoherent radars: solutions for EISCAT Svalbard radar - T. Turunen; J. Markkanen; A. P. van Eyken (Annales Geophysicae, 2000)
Incoherent scatter radars measure ionosphere parameters using modified Thomson scatter from free electrons in the target (see e.g. Hagfors, 1997). The integrated cross section of the ionospheric scatterers is extremely small and the measurements can easily be disturbed by signals returned by unwanted targets. Ground clutter signals, entering via the antenna side lobes, can render measurements at the nearest target ranges totally impossible. The EISCAT Svalbard Radar (ESR), which started measurements in 1996, suffers from severe ground clutter and the ionosphere cannot be measured in any simple manner at ranges less than about 120–150 km, depending on the modulation employed. If the target and clutter signals have different, and clearly identifiable, properties then, in principle, there are always ways to eliminate the clutter. In incoherent scatter measurements, differences in the coherence times of the wanted and unwanted signals can be used for clutter cancellation. The clutter cancellation must be applied to all modulations, usually alternating codes in modern experiments, used for shorter ranges. Excellent results have been obtained at the ESR using a simple pulse-to-pulse clutter subtraction method, but there are also other possibilities. Key words: Radio science (ionospheric physics; signal processing; instruments and techniques)